Equity effects of energy affordability interventions - Niall Farrell (The Economic and Social Research Institute (ESRI), 2023)
This paper compares the distributional effects of price cap and lump sum transfer policies to aid the affordability of subsistence electricity consumption. A lump sum transfer is more progressive than a comparable price cap on all units of electricity. We identify conditions under which these policies have equal distributional effects. We prove that both interventions are progressive.
Keywords: D30; D60; E62; H22; H23; H24; Q4; Q52; Q54; Q58; 330; Elektrizitätsversorgung; Strompreis; Preisregulierung; Öffentliche Sozialleistungen; Verteilungswirkung; Theorie